FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIASI WANITA UNTUK BERWIRAUSAHA DI KABUPATEN PASAMAN BARAT - fitria devi (Horizon, 2021)
This study aims to find out the influence of the influence of husband's role on women's motivation for entrepreneurship, the source of capital on women's motivation for entrepreneurship, self-empowerment of women's motivation for entrepreneurship, education on women's motivation for entrepreneurship and interest in women's motivation for entrepreneurship, influence of husband role, source of capital, self-empowerment, education, interest and motivation jointly influence women's motivation for entrepreneurship in West Pasaman. This type of research is descriptive associative research, the population in this study is women in West Pasaman as many as 440 people with a sample of this study is as many as 50 people using total sampling techniques. Instruments used for research in the form of open and closed questionnaires. Data analysis techniques are descriptive analysis and inductive analysis. The results of this study showed that: 1) The role of husbands has a significant effect on women's motivation to be entrepreneurial with a regression coefficient of 0.235. The coefficient value is significant because the thitung value is 3,650> ttabel is 2.0141. 2) the source of capital has no significant effect on the motivation of women to be entrepreneurial where at the value of x2 loglikelihood ratio which shows x2 count< x2tabel thus means receiving HO which means receiving eliminating the capital source variable (x2). 3) self-empowerment has a significant effect on women's motivation to be entrepreneurial with a regression coefficient value of 0.464. The coefficient value is significant because the thitung value is 4,069 > ttabel of 2.0141.  4) Education has no significant effect on women's motivation to be entrepreneurial with the value of x2 calculate likelihood ratio which shows x2 count< x2tabel thus means receiving HO which thus accepting eliminates educational variables (x4). 5) interest has a significant effect on women's motivation to be entrepreneurial with a regression coefficient value of 0.308. thitung of 3,254 > ttabel of 2.0141. The role of husband, source of capital, self-empowerment, education and interest in women's motivation for entrepreneurship where obtained A value of FCalculated 25,350> FTabel 2.40 means Ho reject Ha accepted.